GE_GERICHTE P/24958/2021 vom 26. August 2022 - GE Cour de justice (2022)
INTÉRÊT JURIDIQUEMENT PROTÉGÉ;QUALITÉ POUR AGIR ET RECOURIR;FAUX INTELLECTUEL DANS LES TITRES;ESCROQUERIE | CPP.382; CPP.115; CP.251; CP.146